A Taxonomy of Construction Material Reuse and Recycling: Designing for Future Disassembly - Crowther, Philip (European Journal of Sustainable Development, 2018)
The construction and demolition industry accounts for approximately one third of all material waste in the industrialised nations of the world. This material and energy waste can however be reduced through increased levels of material and component reuse. A strategy of design for disassembly has been well implemented in product design and manufacture, but the construction industry has failed to adopt such approaches, largely due to the more bespoke nature of architectural projects. This paper explores the technological options for material and component disassembly in buildings. The research projects utilises inductive reasoning to conduct a number of architectural case studies, observing the reoccurring patterns of design that have facilitated material disassembly, then proposes a model or taxonomy of recycling and reuse strategies. The case studies reveal a hierarchy of recycling potentials, each facilitated by different strategies of design for disassembly. This hierarchical taxonomy of recycling can be used to guide design decisions at the early stages of architectural projects; thus increasing the potential for material and component recovery, and reduce negative environmental impact at the future stage of building obsolescence. The paper concludes with design principles, linked to the taxonomy of reuse and recycling.